Penerapan Model Pembelajaran Discovery Learning dalam Meningkatkan Keterampilan Proses Sains Peserta Didik Sekolah Dasar Kabupaten Madiun - Setiawati, Pipit; Mersina Mursidik, Elly’s; Sujianti, Reni (Green Publisher Indonesia, 2024)
Science process skills are skills used by scientists in forming knowledge in solving problems. KPS itself can be improved using the Discovery learning model, a learning method that requires teachers to be more creative in creating situations that encourage students to actively learn and discover their own knowledge. The research method used is classroom action research (CAR) through three stages, namely pre-cycle, cycle I, and cycle II. The research subjects came from 14 fourth grade students. This study used data collection techniques using written tests and observations. The percentage of science process skills was 85.71%. Based on this study, it can be concluded that the use of the discovery learning model can improve students' science process skills.